2020
DOI: 10.5937/scriptamed51-26870
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical pathways on healthcare quality improvement in hospitals for patient undergoing total hip replacement

Abstract: Background: Clinical pathways are important tools to achieve better quality of care and to reduce the costs for healthcare system. The total hip replacement (THR) is among the most expensive procedures in health system and the number of these operations has greatly increased in the past decade in the Republic of Srpska. Aim: The aim of the present study was to determine how the implementation of a clinical pathway for THR can influence the length of stay and postoperative complications in hospitals in the Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[12][13][14] The importance of guidelines implementation at primary and secondary level in RS/B&H was investigated in the past as well. 7,15 The results of this study showed a decreasing number of hypertensive patients with irregular BP level after CVRAM training workshop. Majority of hypertensive patients had a well-controlled BP and the percentage of those with achieved target values was significantly increased after the training workshop of FMTs.…”
Section: Discussionmentioning
confidence: 61%
“…[12][13][14] The importance of guidelines implementation at primary and secondary level in RS/B&H was investigated in the past as well. 7,15 The results of this study showed a decreasing number of hypertensive patients with irregular BP level after CVRAM training workshop. Majority of hypertensive patients had a well-controlled BP and the percentage of those with achieved target values was significantly increased after the training workshop of FMTs.…”
Section: Discussionmentioning
confidence: 61%
“…The arthroplasty theatre complexes were equivalent in both hospitals, but laminar flow was only available in the TH operating rooms. Similar clinical pathways for arthroplasty surgery were used in both hospitals including antiseptic skin preparation, sterile surgical site draping and antibiotic prophylaxis as recommended by the NICE guidelines [ 25 – 28 ]. Patients received one dose of first-generation Cephalosporin antibiotic; or Clindamycin for those with penicillin allergy; prior to skin incision and 3 doses postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…8 The other main impression is contained in the obituary honouring late Professor Folke Sjöqvist, one of the founders of clinical pharmacology as a discipline in Europe, 9 to whom many of us and the entire discipline are indebted to. Since our journal covers all fields of medicine, the remaining articles bring the results of some basic pharmacological experiments on the role of GABA A receptors in vasodilation, 10 on the role of clinical pathways in quality improvement in patients undergoing total hip replacement 11 and describe some clinical studies performed in the fields of ophthalmology 12 and hepatic resections in metastatic colorectal cancer surgery, 13 followed by a case report on hypofibrinogenaemia in pregnancy. 14 Of course, the Editorial Board will continue to follow the COVID-19 pandemic as it evolves, but at the same time will try to provide to its readers coverage of all other interesting topics.…”
mentioning
confidence: 99%